2015
DOI: 10.1186/s12886-015-0154-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary silicone oil tamponade and internal limiting membrane peeling for retinal detachment due to macular hole in highly myopic eyes with chorioretinal atrophy

Abstract: BackgroundRetinal detachment (RD) secondary to macular hole (MH) is a common complication in highly myopic eyes, usually leading to a poor visual prognosis. The purpose of this study was to evaluate the surgical outcome of silicone oil (SO) tamponade and internal limiting membrane (ILM) peeling in the treatment of RD caused by MH (MHRD) in highly myopic eyes with chorioretinal atrophy, and to identify clinical factors associated with the anatomical outcomes.MethodsWe retrospectively reviewed 21 eyes of 21 high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The authors did not comment on the type of macular hole closure. Hong et al 9 reported 76.2% and 100% retinal re-attachment rates after primary and repeat surgeries, respectively. Macular hole closure rate was 61.9% after primary surgery and 76.2% after repeat surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors did not comment on the type of macular hole closure. Hong et al 9 reported 76.2% and 100% retinal re-attachment rates after primary and repeat surgeries, respectively. Macular hole closure rate was 61.9% after primary surgery and 76.2% after repeat surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Hence, several alternative techniques were introduced for MRDMH, though with no consensus to date among retina surgeons on one optimal surgical approach. [6][7][8][9][10][11][12] Some authors advocated that a longer term tamponade provided by silicone oil could improve the surgical outcome of MRDMH patients for several reasons. Firstly, silicone oil provides the desired tamponade effect while averting centrifugal overstretch of the inelastic retina around the hole.…”
Section: Introductionmentioning
confidence: 99%
“…Peeling away the ILM can not only relax the adhesions of the macula of the vitreous and completely relieve the traction of the posterior boundary membrane of the vitreous on the macula but also reduce the adhesion of VEGF, inflammatory factors and other related vasoactive factors and reduce the recurrence rate of vitreous macular interface disease. Consequently, PPV with ILM peeling has been applied in the surgical treatment of fundus diseases, especially in MHs, ME, macular epiretinal membranes, retinal splitting and other tractive macular diseases [9]. The need for combined ILM peeling in patients with DME, however, is currently controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Silikon 1000, in the form of silicone oil or polydimethylsiloxane, has been used as vitreous substitute to treat difficult cases of retinal detachment as well as medical devices for prosthetic and cosmetic purposes [43,44]. Silicone injection is believed to be theoretically inert for decades but now is thought to be a potential cause for direct and indirect toxic effects in biological system [52–54].…”
Section: Resultsmentioning
confidence: 99%
“…When the DART source is coupled to different mass spectrometers, it provides a rapid MS analysis of a wide range of compounds [3539], where its mechanism and applications are described elsewhere and summarized in a couple of reviewpapers [33,34]. In this study DART-MS is introduced for the first time to measure the presence of bacterial endotoxin in OVD materials, including sodium hyaluronate (NaHA) [40], perfluoro- n -octane (PFO) [41,42], and silicone oil (SO) [43,44]. Sodium hyaluronate is currently the most popular viscoelastic injection for a variety of intraocular surgical procedures such as cataract extraction, lens implantation and retina attachments since the 1970s.…”
Section: Introductionmentioning
confidence: 99%